Food allergens : best practices for assessing, managing and communicating the risks - Fu, Tong-Jen; Jackson, Lauren S.; Krishnamurthy, Kathiravan; Bedale, Wendy (Springer, 2018)
This volume identifies gaps in the assessment, management, and communication of food allergen risks. Chapters showcase best practices in managing allergen risks at various stages of the food chain, including during food manufacture/processing; during food preparation in food service, retail food establishments, and in the home; and at the point of consumption. The authors highlight key legislative initiatives that are in various stages of development and implementation at the federal, state and community levels. Finally, the volume includes recommendations for ways to build and strengthen education and outreach efforts at the food industry, government, institutional, and community levels. Chapters come from an array of experts, including researchers and key stakeholders from government, the food industry, retail/food service groups, and consumer groups. The information presented will facilitate the development of educational materials and allergen management training programs for food production and service staff, extension specialists, and government inspectors. Consumers and other food safety professionals will also benefit from information on food allergen control measures that have been put in place across the food chain.- Resumé vydavatel
Keywords: potravinové alergeny; veřejné zdraví; potravinářská mikrobiologie; food allergens; public health; food microbiology; electronic books; papers of several authors; sborníky; elektronické knihy